SISTEM INFORMASI COMPUTER BASED TEST (CBT) SEBAGAI SARANA PENILAIAN BELAJAR SISWA DI MA SUNAN PRAWOTO - Muhamad Arifin; Sudargo Sudargo; Ika Menarianti (Universitas PGRI Semarang, 2021)
Along with the development of education in the industrial era 4.0, it is a demand for the world of education to be able to apply the use of digital technology in the learning process. The application of information technology related to the computer-based student learning evaluation process has attracted the interest of many educational institutions to apply it. Examination that still uses conventional mode usually requires a lot of time, money and effort. Especially in the current pandemic era, learning must be carried out online. Besides the government has determined the implementation of exams using the CBT method for Elementary School (SD) to Senior High School (SMA) levels, the use of the CBT test system can also reduce several problems such as: reducing thel evel of student cheating (cheating), reducing budget costs , and the time it takes to be more effective. The aim of this research is to design and build a web-based CBT information system application that can facilitate student evaluation at MA Sunan Prawoto. The method used in this research is the Research and Development (R&D) method with the waterfall development mode, where the stages include: Communication, Planning, Modeling, Construction and Deployment stages with system design including: Flowchart System Design, Context Diagram, DFD, ERD, Design Tables and DIPO. This research is then implemented into the PHP programming language using the MySQL database. The CBT information system application has been generated. In the testing process through 2 expert validations, an average percentage of 90.6% was obtained where the percentage was included in the very feasible category, while the test results using a user response questionnaire obtained an average percentage of 90.5%, where the percentage is also included in the very decent category.